COHESIVE DEVICES IN RICHARD B. PELZER’S MEMOIR: A BROTHER’S JOURNEY - Fatimah Z. Siregar and Amrin Saragih (LINGUISTICA, 2017)
The study deals with the types of cohesive devices in Richard B. Pelzer‟s memoir, A Brother‟s Journey. The objectives of this research were to find out the types of cohesive devices, the dominant type of cohesive devices and to describe the implication of the dominant type of cohesive devices of it. This research was conducted by using descriptive qualitative design. The data were 538 sentences taken from 18 chapters and first 2 pages from the each page which were collected by applying documentary technique. The five types of cohesive devices occurred in a text of A Brother‟s Journey, namely reference (62, 29%), substitution (0, 94%), ellipsis (2, 07%), conjunction (34, 32%), and lexical cohesion (0, 36 %). The dominant type of cohesive devices was reference. The implication of using reference dominantly in this text was to help the writers to keep the identity of the participants, ideas and things in the story and keep track them through the story. By using reference, the writer had the ability to avoid unnecessary repetition so that the readers easily get the information about an item that indicates the identity of what is being talked about from the text. From those findings, it is concluded that cohesive devices plays an important roles in written.